EVALUATION OF CONTRAST‐ENHANCED ULTRASONOGRAPHY AS A METHOD FOR DETECTING GALLBLADDER NECROSIS OR RUPTURE IN DOGS. Issue 6 (30th August 2016) - Bargellini, Paolo; Orlandi, Riccardo; Paloni, Chiara; Rubini, Giuseppe; Fonti, Paolo; Peterson, Mark E.; Rishniw, Mark; Boiti, Cristiano
Abstract : Gall bladder necrosis and rupture are life‐threatening conditions in dogs requiring surgical intervention and early diagnosis is essential. Human patients with suspected gall bladder necrosis/rupture are commonly evaluated with contrast‐enhanced ultrasonography (CEUS), however this procedure has not been described in dogs with suspected gall bladder necrosis/rupture. In a prospective diagnostic cohort study, CEUS (using SonoVue contrast medium) was performed in 93 dogs with gallbladder lesions identified by abdominal conventional ultrasonography. Necrosis/rupture was identified by CEUS as a focal lack of enhancement of the gallbladder wall. Dogs with positive CEUS finding for necrosis/rupture (complete lack of regional wall enhancement) underwent immediate surgery as did dogs with other biliary disorders requiring surgery. Dogs with negative CEUS findings or those not requiring surgery were managed medically. In cases undergoing surgery, necrosis/rupture was confirmed intraoperatively (and via histopathology). Absence of necrosis/rupture was confirmed either intraoperatively (via histopathology) or was assumed to be absent by complete recovery with medical management. Forty‐nine dogs underwent surgery and cholecystectomy: 24 had necrosis/rupture. CEUS was more accurate (100% sensitive and specific) in diagnosing gallbladder wall necrosis/rupture than conventional ultrasonography (75% sensitive and 81% specific) ( P < 0.03). In conclusion, CEUS provides accurate characterization of gallbladder wall integrity that can impact decisions regarding clinical management, either surgical or medical.